The social semantics of education: Empirical study on a sample of school actors - Meksen, Asma; Amireche, Nedjoua (Journal of Human Sciences, 2022)
This exploratory study came to identify the social semantics of school actors, in this study we followed the descriptive approach by conducting a field interview on an intentional sample of 15 teachers from primary education in the municipality of El Harrouch-Skikda. After analyzing the data obtained, the study concluded that the process of forming these social semantics of education takes place through the processes of interaction and social conflict within the school organization, between the interests particulars of each actor and the general interests of the organization as a whole, and that the social semantics of teaching programs and the educational relationship had not yet deviated from their traditional conception.